2013
DOI: 10.1097/wno.0b013e31825be577
|View full text |Cite
|
Sign up to set email alerts
|

Sheehan Syndrome Associated With Raised Intracranial Pressure

Abstract: This case supports a causal role of hypocortisolism in IH. The authors are unaware of previous reports of hypocortisolism caused by SS leading to IH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…4,7,[10][11][12] The clinical manifestations include non-specific complaints such as asthenia, weakness and fatigue, signs of loss of axillary or pubic hair, dry skin, hypopigmentation, hypotension, hypoglycemia and other hypopituitarism symptoms. [13][14][15][16][17] In our study, the diagnosis delay of Sheehan's syndrome was 1 month to 35 years and the mean duration was 9.1±9.5 years. We found that massive bleeding at delivery, failure to resume menstruation, agalactia and signs of axillary or pubic hair loss were very important clues for identification of Sheehan's syndrome.…”
Section: Discussionmentioning
confidence: 48%
“…4,7,[10][11][12] The clinical manifestations include non-specific complaints such as asthenia, weakness and fatigue, signs of loss of axillary or pubic hair, dry skin, hypopigmentation, hypotension, hypoglycemia and other hypopituitarism symptoms. [13][14][15][16][17] In our study, the diagnosis delay of Sheehan's syndrome was 1 month to 35 years and the mean duration was 9.1±9.5 years. We found that massive bleeding at delivery, failure to resume menstruation, agalactia and signs of axillary or pubic hair loss were very important clues for identification of Sheehan's syndrome.…”
Section: Discussionmentioning
confidence: 48%